Decreased allopregnanolone levels in cerebrospinal fluid obtained during status epilepticus. (26th November 2016) - Meletti, Stefano; Lucchi, Chiara; Monti, Giulia; Giovannini, Giada; Bedin, Roberta; Trenti, Tommaso; Rustichelli, Cecilia; Biagini, Giuseppe
Summary: Neuroactive steroids are increasingly considered as relevant modulators of neuronal activity. Especially allopregnanolone (AP) and pregnenolone sulfate (PS) have been shown to possess, respectively, anticonvulsant or proconvulsant properties. In view of the potential role of these steroids, we aimed at evaluating AP and PS levels in cerebrospinal fluid (CSF) and blood samples obtained from patients with status epilepticus (SE). To this purpose, we enrolled 41 patients affected by SE and 41 subjects investigated for nonepileptic neurologic disorders. Liquid chromatographic procedures coupled with electrospray tandem mass spectrometry and routine laboratory investigations were performed. Significantly lower AP levels were found in the CSF of patients affected by SE (−30%; p < 0.05, Mann‐Whitney test). Notably, AP was not detectable in 28 of 41 patients affected by SE (p < 0.01 vs. controls, Fisher's exact test). In serum, AP levels did not differ in the two considered groups. Conversely, PS was present at similar levels in the investigated groups. Finally, differences in AP levels could not be explained by a variation in CSF albumin content. These findings indicate that AP is defective in the CSF of patients affected by SE. This phenomenon was not dependent on carriers for steroids, such as albumin.